Perempuan dan Perubahan di Perdesaan: Studi Kasus Lurah Sriharjo, Kabupaten Bantul - Nefa Wahyuning Anggraini; Andre Dwi Prasaja (JPP (Jurnal Politik Profetik), 2024)
Village governments is a vital autonomous institutions based on Law Number 6 of 2014 concerning Villages. Sriharjo village is one example of local democracy with its first female village head. During the leadership of the Sriharjo village head, there were obstacles and challenges, particularly in the political dynamics of Sriharjo village. The aim of this research is to analyze women's leadership in the implementation of village government policies in line with the political dynamics in Kalurahan Sriharjo. The theoretical foundation of this research uses Bass and Avolio's transformational leadership. This study uses a qualitative intrinsic case study method based on Robert K. Yin. Data was obtained through observation, interviews, and documentation. The research results indicate that the leadership of the Sriharjo village head has brought significant changes in terms of policies and social and political institutions. Essentially, the village head is not solely focused on power to manage the government; the most important aspect is the elaboration for sustainable development. Efforts to improve Sriharjo require a long process and the involvement of various parties, including supra-village levels.